Association Between the Severity of Chronic Obstructive Pulmonary Disease and the Probability of Pulmonary Hypertension In a Tertiary Hospital - Handayani, Friska; Herman, Deddy; Fitrina, Dewi Wahyu (Jurnal Respirologi Indonesia, 2025)
Background: Chronic obstructive pulmonary disease (COPD) patients with pulmonary hypertension (PH) have a poor prognosis, which worries doctors. The prevalence of COPD-related PH is unclear. The lack of anatomical criteria for right ventricular hypertrophy may explain research variance. Only type 1 PH patients undergo direct right cardiac catheterization of pulmonary artery pressure. Methods: A cross-sectional analytical descriptive study examined stable COPD patients visiting the pulmonary department at M. Djamil Hospital, Padang, from November 2023 to February 2024 for PH probability. Results: This study included 64 participants, with a majority aged between 40 and 65 years (59.4%), a significant proportion male (82.8%), and a junior high school (29.7%) level of education. Most of the subjects smoked (81.2%), had severe Brinkman Index (75.0%), had severe GOLD criteria (50.0%), and had no comorbidities (53.1%). No correlation was found between the severity of COPD and the likelihood of PH (P=0.591). The Brinkman Index of smokers was a significant risk factor for PH (P=0.010; OR=1.282; 95% CI=0.260-6.315).  Conclusion: There is no significant association between the severity of COPD according to GOLD criteria and the likelihood of PH.